Meningkatkan Hasil Belajar Peserta Didik dengan Model Discovery Learning pada Materi Ikatan Kimia - Lathifah Nur'aini Sariwati; Agus Sunaryo; Sukarmin Sukarmin (Hydrogen: Jurnal Kependidikan Kimia, 2023)
This study aims to improve student learning outcomes with the Discovery Learning learning model on chemical bonding material for class X-6 SMAN 2 Ponorogo. This research is a Classroom Action Research (PTK) which consists of three cycles. This cycle in PTK uses the Lesson Study format which includes planning (Plan), implementation (Do), and reflection (See). Data collection techniques include test techniques in the form of knowledge aspect tests, while the non-questionnaire technique is peer assessment and observation. In this study, student learning outcomes cover 3 aspects, namely aspects of knowledge, attitudes and skills. The learning outcomes of students in the knowledge aspect in cycle I amounted to 47.2% increasing to 67% in cycle II then in cycle III increasing to 86%. While the learning outcomes of students in the attitude aspect in cycle I had an average of 3.13 in cycle I increased to 3.28 in cycle II then in cycle III an average of 3.43 was obtained. The learning outcomes of students in the skills aspect in cycle I obtained an average of 3.03 and increased in cycle II of 3.28 then in cycle III the average increased to 3.35. The conclusion of this study shows that student learning outcomes increase by using the Discovery Learning learning model.